2012
DOI: 10.1371/journal.pone.0042433
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of DNA Methylation in Development, Division of Labor and Hybridization in an Ant with Genetic Caste Determination

Abstract: BackgroundDNA methylation is a common regulator of gene expression, including acting as a regulator of developmental events and behavioral changes in adults. Using the unique system of genetic caste determination in Pogonomyrmex barbatus, we were able to document changes in DNA methylation during development, and also across both ancient and contemporary hybridization events.Methodology/Principal FindingsSodium bisulfite sequencing demonstrated in vivo methylation of symmetric CG dinucleotides in P. barbatus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 56 publications
(83 reference statements)
4
35
0
Order By: Relevance
“…We found that high levels of DNA methylation (mCG/CG) correspond well with CpG depletion in exons (Spearman's R = À0.53) ( Fig. 3B; Supplemental Tables 11,12), indicating that some genes in ants are distinguished by DNA methylation, similar to the honeybee (see also Bonasio et al 2012;Smith et al 2012). Functional analysis of genes putatively methylated in all seven ant genomes (low CpG O/E) revealed enrichment for housekeeping functions, including transcription, translation, and cellular metabolic function (FDR < 0.05) (Supplemental Tables 13-15), as reported for the honeybee (Elango et al 2009).…”
Section: Ant Conserved Regions Harbor An Abundance Of Regulatory Elemmentioning
confidence: 71%
See 1 more Smart Citation
“…We found that high levels of DNA methylation (mCG/CG) correspond well with CpG depletion in exons (Spearman's R = À0.53) ( Fig. 3B; Supplemental Tables 11,12), indicating that some genes in ants are distinguished by DNA methylation, similar to the honeybee (see also Bonasio et al 2012;Smith et al 2012). Functional analysis of genes putatively methylated in all seven ant genomes (low CpG O/E) revealed enrichment for housekeeping functions, including transcription, translation, and cellular metabolic function (FDR < 0.05) (Supplemental Tables 13-15), as reported for the honeybee (Elango et al 2009).…”
Section: Ant Conserved Regions Harbor An Abundance Of Regulatory Elemmentioning
confidence: 71%
“…Given the abundance of conserved regulatory elements in ant genomes, we examined three mechanisms previously implicated in the regulation of social traits or phenotypic plasticity: direct modification of DNA by methylation (Kucharski et al 2008;Bonasio et al 2012;Smith et al 2012), transcriptional and translational regulation by small RNAs (Pauli et al 2011), and transcriptional regulation by transcription factors (TFs) (Rebeiz et al 2011).…”
Section: Ant Conserved Regions Harbor An Abundance Of Regulatory Elemmentioning
confidence: 99%
“…The sequencing of more species with different levels of plasticity and multiple phenotypes will be required to confirm this hypothesis (6). However, the available data suggest that these hallmarks contrast with those hallmarks of eusocial insects with low plasticity like the honey bee and most ants, where a large proportion of genes, functionality, and network differentiation are associated with phenotypic differentiation (44,(53)(54)(55)(56)(57)(58), and where phenotypes appear to be regulated by DNA methylation (24,25,30,34,35,37,(59)(60)(61)(62). Comparisons of species with contrasting evolutionary histories, as in our study species, will be especially valuable in revealing the molecular signatures at the origin of social evolution (e.g., in P. canadensis) and in reversions from complex to simple behaviors (e.g., in D. quadriceps).…”
Section: Discussionmentioning
confidence: 99%
“…These modifications exert epigenetic control that suppresses or activates gene expression (Smith et al. 2012). …”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation is potentially important in shaping phenotypes and adaptations to the environment, such as in caste determination in eusocial species (Smith et al. 2012; ‏Yan et al. 2014; but see Libbrecht et al.…”
Section: Introductionmentioning
confidence: 99%